Two new species of Tibouchina (Melastomataceae) from the Brazilian Cerrado - Schmitz Meyer, Fabrício; de Oliveira Diniz, Danielle; Klostermann Ziemmer, Juliana; Goldenberg, Renato (Phytotaxa, 2023)
We describe here two new species of Tibouchina from the Brazilian Cerrado. Tibouchina falcifolia is endemic to the state of Goiás and it can be readily recognized by the lanceolate to linear, conduplicate, pendulous leaves, and very conspicuous hypanthium scales. It is morphologically related to Tibouchina aegopogon var. angustifolia, especially by the narrow leaves, but differs by the older branches decorticant (vs. older branches non-decorticating), slightly discolorous leaves (vs. strongly discolorous leaves), with the adaxial surface covered by trichomes (vs. covered by scales). Tibouchina longisquamata is a species endemic to the state of Tocantins and it can be readily recognized by the oval, flat, patent leaves and hypanthium with long scales. It shares with Tibouchina llanorum the oval, slightly discolorous leaves, with a conspicuous petiole, and hypanthium covered with long scales. Tibouchina longisquamata differs from T. llanorum by its subcylindrical branches (vs. 4-6 angulose) and leaves with the adaxial surface covered by trichomes (vs. covered by scales). According to our assessments, based on IUCN criteria, T. falcifolia must be considered as endangered (EN) because its occurrence is restricted, and its populations are small; T. longisquamata is indicated in Deficient Data (DD), with only two known collections. We present here complete descriptions of the new species, taxonomic comments, illustrations made from dehydrated material, photos of live specimens (for T. falcifolia), plates with microscopic details, a distribution map, and an updated list of species of the genus in the Brazilian Cerrado, with its occurrences by state.